Research training: Validating a key questionnaire on systematic reviews and meta-analysis for medical genetics residents in Mexico - Luis Felipe León Madero; Valentina Martínez Montoya; Franahid Josefina D'silva Signe (Educación Médica, 2025)
Introduction: Systematic reviews and meta-analyses are critical in Evidence-Based Medicine, representing the highest level of scientific evidence. Despite the inclusion of Research Methodology and Statistics in medical curricula, the publication rate among residents remains low. This study focuses on residents in the Medical Genetics specialty in Mexico City, illustrating challenges faced in a developing country. Methods: Using both qualitative and quantitative methods, from the perspective of the Curriculum Action Research movement, the study surveyed 25 residents from eight hospitals in Mexico City. The information was collected using the proposed evaluation instrument, which was modified for validation. Results: In this study, we showed that 64% had published work, but only 12.5% had completed systematic reviews. A significant proportion perceived not receiving formal training in Research Methodology (4%) or Statistics (52%). Key barriers identified were lack of time (56%), insufficient research experience (46%), cost or lack of resources (44%), and the administrative procedures required being very complicated (44%). The study developed and validated a questionnaire to assess knowledge, which demonstrated good reliability and construct validity with a Cronbach’s alpha of 0.85, a Kaiser-Meyer-Olkin (KMO) measure of 0.505 and a significant Bartlett's test of sphericity (p<0.0001). Conclusions: The findings highlight substantial gaps in practical research skills and suggest that the current curriculum inadequately integrates Research Methodology and Statistics. This underscores the need for more effective incorporation of these subjects into training programs to enhance residents' research capabilities. Addressing these gaps could improve publication rates and overall research output among medical residents. Resumen: Introducción: Las revisiones sistemáticas y los meta-análisis son fundamentales en la Medicina Basada en Evidencia, representando el nivel más alto de evidencia científica. A pesar de la inclusión de la Metodología de la Investigación y la Estadística en los programas académicos de Medicina, la tasa de publicación entre los residentes sigue siendo baja. Este estudio se enfoca en los residentes de la especialidad de Genética Médica en la Ciudad de México, ilustrando los desafíos enfrentados en un país en desarrollo. Métodos: Utilizando métodos cualitativos y cuantitativos, desde la perspectiva del movimiento de Investigación-Acción Curricular, el estudio encuestó a 25 residentes de ocho hospitales en la Ciudad de México. La información se recopiló utilizando el instrumento de evaluación propuesto, el cual fue modificado para su validación. Resultados: En este estudio mostramos que el 64% de los estudiantes de especialidad había publicado trabajos, pero solo el 12.5% había realizado revisiones sistemáticas. Una proporción significativa percibió no haber recibido formación formal en Metodología de la Investigación (4%) ni en Estadística (52%). Las principales barreras identificadas fueron la falta de tiempo (56%), la experiencia insuficiente en investigación (46%), el costo o la falta de recursos (44%) y que los procedimientos administrativos requeridos eran muy complicados (44%). El estudio desarrolló y validó un cuestionario para evaluar el conocimiento en esta área, el cual demostró una buena fiabilidad y validez de constructo, con un alfa de Cronbach de 0.85, una medida de Kaiser-Meyer-Olkin (KMO) de 0.505 y una prueba de esfericidad de Bartlett significativa (p<0.0001). Conclusiones: Los hallazgos destacan brechas importantes en las habilidades prácticas en investigación y sugieren que el currículo actual integra de manera insuficiente la Metodología de la Investigación y la Estadística. Esto subraya la necesidad de una incorporación más efectiva de estos temas en los programas de formación para mejorar las capacidades de investigación de los residentes. Abordar estas brechas podría mejorar las tasas de publicación y la producción general en investigación entre los residentes médicos.